A SYSTEM CAN FILTER THE UNWANTED MESSAGES FROM OSN WALLS - G, Kumutha (International Journal of Scientific Research and Management (IJSRM), 2014)
themessages posted on their own private space to avoid that unwanted content is displayed. Up to now OSNsprovide little support to this requirement. To fill the gap, in this paper, we propose a system allowing OSNusers to have a direct control on the messages posted on their walls. This paper focuses on a newincremental method for updating approximations of system wall , while objects in the information systemdynamically alter. It discusses properties of information granulation and approximations under the dynamicenvironment while objects in the universe evolve over time. The variation of an attribute’s domain is alsoconsidered to perform incremental updating for approximations under the system walls. Finally, anextensive experimental evaluation validates the efficiency of the proposed method for dynamic maintenanceof VPRS approximations One fundamental issue in today On-line Social Networks (OSNs) is to give users the ability to control